2013
DOI: 10.1055/s-0032-1328144
|View full text |Cite
|
Sign up to set email alerts
|

Single-center results at 7 years of prospective, randomized ProDisc-C total disc arthroplasty versus anterior cervical discectomy and fusion for treatment of one level symptomatic cervical disc disease

Abstract: Study design: Prospective randomized controlled study.Introduction: Symptomatic cervical disc disease (SCDD) causing radiculopathy is a common diagnosis traditionally treated surgically with anterior cervical discectomy and fusion (ACDF).Objective: The purpose of this trial is to compare the safety and effi cacy of total disc arthroplasty (TDA) using the ProDisc-C (Synthes Spine Company, LP, West Chester, PA, USA) implant to ACDF in patients with single-level SCDD between C3 and C7.Methods: This study is a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…They used single-site data which is part of a multicenter trial or missed some important data. In the same time, many randomized controlled trials (RCTs) comparing CDA with ACDF for the treatment of CDDDs were performed (Burkus et al 2010 , 2014 ; Cheng et al 2009 , 2011 ; Coric et al 2011 ; Davis et al 2013 ; Delamarter and Zigler 2013 ; Delamarter et al 2010 ; Davis et al 2015 ; Hisey et al 2014 , 2015 ; Heller et al 2009 ; Kesman et al 2012 ; Kelly et al 2011 ; McAfee et al 2010 ; Mummaneni et al 2007 ; Murrey et al 2008 , 2009 ; Phillips et al 2013 , 2015 ; Nabhan et al 2007a , b , c , 2011 ; Porchet and Metcalf 2004 ; Qizhi et al 2014 ; Riina et al 2008 ; Riew et al 2008 ; Rozankovic et al 2014 ; Sasso et al 2007 , 2008 , 2011 ; Skeppholm et al 2015 ; Vaccaro et al 2013 ; Zhang et al 2012 , 2014 ; Zigler et al 2013 ). Therefore, an updated meta-analysis is needed which is based on the latest high quality studies.…”
Section: Introductionmentioning
confidence: 99%
“…They used single-site data which is part of a multicenter trial or missed some important data. In the same time, many randomized controlled trials (RCTs) comparing CDA with ACDF for the treatment of CDDDs were performed (Burkus et al 2010 , 2014 ; Cheng et al 2009 , 2011 ; Coric et al 2011 ; Davis et al 2013 ; Delamarter and Zigler 2013 ; Delamarter et al 2010 ; Davis et al 2015 ; Hisey et al 2014 , 2015 ; Heller et al 2009 ; Kesman et al 2012 ; Kelly et al 2011 ; McAfee et al 2010 ; Mummaneni et al 2007 ; Murrey et al 2008 , 2009 ; Phillips et al 2013 , 2015 ; Nabhan et al 2007a , b , c , 2011 ; Porchet and Metcalf 2004 ; Qizhi et al 2014 ; Riina et al 2008 ; Riew et al 2008 ; Rozankovic et al 2014 ; Sasso et al 2007 , 2008 , 2011 ; Skeppholm et al 2015 ; Vaccaro et al 2013 ; Zhang et al 2012 , 2014 ; Zigler et al 2013 ). Therefore, an updated meta-analysis is needed which is based on the latest high quality studies.…”
Section: Introductionmentioning
confidence: 99%
“…To date there have been several published reports of randomized controlled trials comparing ACDF with AD replacement with varying results. 4,21,35,48,64,70,71 The results of these trials have shown that AD replacement has excellent outcomes and in some instances is superior to ACDF with lower reoperation rates as well as improved clinical outcomes. Biomechanical studies are important to better understand neck function postsurgery and may provide insight into the mechanical factors that contribute to a good or poor clinical outcome.…”
mentioning
confidence: 99%
“…44 Murrey et al (200844 Murrey et al ( , 2009, Delamarter et al (2010), Kelly et al (2011), Kesman et al (2012), Zigler et al (2013), Zigler et al (2013)[48][49][50][51][52][53][54] …”
mentioning
confidence: 99%